2020
DOI: 10.1186/s40008-020-00224-2
|View full text |Cite
|
Sign up to set email alerts
|

Uganda’s experience with debt and economic growth: an empirical analysis of the effect of public debt on economic growth—1980–2016

Abstract: Background: Empirical evidence on the effect of public debt on the economic growth of a country remains ambiguous. No theoretical convergence on the respective nexus has been attained. For the case of Uganda in particular, the public debt question remains critical in the country's development trajectory. Under the Highly Indebted Poor Countries (HIPCs) initiative, Uganda was the first country to receive a debt relief of worth US$650 million in the 1990s and later in 2006, under the Multilateral Debt Relief Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Although Uganda's GDP has improved since 2010, save for the two years of Covid-19 (2020Covid-19 ( -2022, the economy is still fragile to compete, generate jobs, increase incomes, and provide products and services to the population in desirable amounts (Ellen & Peter, 2016;Oxfam, 2016). This is in congruence with Ssempala, Ssebulime, and Twinoburyo (2020) whose claims allude to the view that the borrowed monies from the World Bank, IMF, and Exim Bank have in many ways affected Uganda's GDP to persuade one to think that the economy is doing well whereas not. Economic growth and university education are inseparable; therefore, refocusing our energy and resources into university business by way of recontextualizing the curricula to the local realities, empowering academics in all fields by granting them academic freedom and independence, adopting purposeful yet stimulating teaching and learning techniques, extending reasonable funding to researchers, and mindset transformation of all key stakeholders may become a good step in realizing the long-awaited innovation in Uganda's Higher Education (HE).…”
Section: Problem Statementsupporting
confidence: 60%
“…Although Uganda's GDP has improved since 2010, save for the two years of Covid-19 (2020Covid-19 ( -2022, the economy is still fragile to compete, generate jobs, increase incomes, and provide products and services to the population in desirable amounts (Ellen & Peter, 2016;Oxfam, 2016). This is in congruence with Ssempala, Ssebulime, and Twinoburyo (2020) whose claims allude to the view that the borrowed monies from the World Bank, IMF, and Exim Bank have in many ways affected Uganda's GDP to persuade one to think that the economy is doing well whereas not. Economic growth and university education are inseparable; therefore, refocusing our energy and resources into university business by way of recontextualizing the curricula to the local realities, empowering academics in all fields by granting them academic freedom and independence, adopting purposeful yet stimulating teaching and learning techniques, extending reasonable funding to researchers, and mindset transformation of all key stakeholders may become a good step in realizing the long-awaited innovation in Uganda's Higher Education (HE).…”
Section: Problem Statementsupporting
confidence: 60%
“…For instance, Owusu-Nantwi and Erickson (2016) showed that a bidirectional relationship with positive effect exists for public debt and GDP in Ghana but a weak association for Nigeria as shown in Ogunmuyiwa (2011). Tchereni et al (2013) produced a statistically insignificant negative relationship for Malawi while the result of the study by Ssempala et al (2020) on Uganda produced mixed long run effects and statistically negative impact in the short run. Saungweme and Odhiambo (2019a) employed a dynamic multivariate ARDL bounds test approach on servicing of debt, public debt, GDP for Zambia and came up with a unidirectional causality result that runs public debt through economic growth.…”
Section: Theoretical and Empirical Reviewmentioning
confidence: 83%
“…This is also consistent with the postulation of the Keynesians that at certain level, public debt can impact positively on growth. Corruption and inflation are negatively and statistically significant in their relationship with economic growth while external debt servicing effect on growth is negative although, it is not statistically significant (see Akram, 2017; Kim et al , 2017; Ssempala et al , 2020). For instance, if corruption increases by 1%, the implication on growth will be 0.28% decrease while a 1% increase in the level of inflation will bring down growth by 0.13%.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Domestic debt that stood at 52% of GDP in 2004 declined to 24% in 2019, whereas foreign debt rose to 78% in 1994 and declined to 38% in 2019 (World Bank, 2020). The direct effect of both trade openness and sovereign debt on economic growth has been extensively investigated in several studies, such as Osei-Assibey and Dikgang (2020), Ssempala et al (2020) and Asteriou et al (2021). However, the interactive effect has not been given due attention, which creates a knowledge gap that needs to be filled.…”
Section: Introductionmentioning
confidence: 99%